2021
DOI: 10.1007/s41208-021-00366-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, in-vitro Antioxidant, Antibacterial, and Anti-algal Activity of Lakshadweep Feather Star Spp. Comaster Schlegelii and Himerometra Robustipinna

Abstract: Crinoids are the least explored class of Echinoderms for their bioactivity. To date, no work has been done to evaluate the pharmacological potential of feather star spp. Comaster schlegelii (SRK1) and Himerometra robustipinna (SRK2). The extracts were tested for antibacterial activity against human pathogens, anti-diabetic potential of the extracts were screened by evaluating the ability of the extract to modulate the enzyme α-amylase, anti-algal and antioxidant activity of the extracts were determined by vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Interest in the chemistry of crinoid-derived natural product is increasing. Antibacterial, antioxidant, anti-diabetic, and anti-algal activities have been reported for two feather star species, Comaster schlegelii and Himerometra robustipinna [ 12 ]. Being sessile animals, crinoids use chemical defense mechanisms including toxic chemical compounds to protect themselves from predators.…”
Section: Echinoderms As a Source Of Various Bioactive Substancesmentioning
confidence: 99%
See 3 more Smart Citations
“…Interest in the chemistry of crinoid-derived natural product is increasing. Antibacterial, antioxidant, anti-diabetic, and anti-algal activities have been reported for two feather star species, Comaster schlegelii and Himerometra robustipinna [ 12 ]. Being sessile animals, crinoids use chemical defense mechanisms including toxic chemical compounds to protect themselves from predators.…”
Section: Echinoderms As a Source Of Various Bioactive Substancesmentioning
confidence: 99%
“…Many studies have reported that echinoderms show significant antidiabetic activity. The ethanolic extracts from the feather stars Comaster schlegelii and Himerometra robustipinna have a moderate inhibitory effect on the enzyme α-amylase [ 12 ]. Extracts from three echinoderms Astropecten irregularis , Luidia sarsi , and Ophiura albida could significantly inhibit amylase and glucosidase involved in the digestion of starch and the glucose production [ 5 ].…”
Section: Echinoderms As a Source Of Various Bioactive Substancesmentioning
confidence: 99%
See 2 more Smart Citations